HOW MILLENIALS FIT IN HOTEL INDUSTRY AFTER THE PANDEMIC - Oqke Prawira Triutama; Adestya Ayu Armielia; Chelsia Pranindyasari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Before the pandemic, the hotel industry thrives worldwide. Hotel industry is a service-based and labor-intensive sector. Although many students pursue careers in the hospitality industry, they usually leave the industry within 6 years. Millennials are the population that currently dominates the workforce in the hotel industry, where the composition exceeds 50% among other generations in the workplace. Given the retention challenges facing the hotel industry, owners or managers need to know the ways in which they must be able to retain their millennial employees. This article investigates the extent to which the recruitment process, working environment conditions, and the information technology systems can influence millennial employees retain in the hotel industry. The validity test in this study was carried out twice on 40 samples by calculating the Pearson Product Moment correlation coefficient. The questionnaire was measured using a Likert scale. Multiple linear regression analysis was performed to test the effect of three independent variables on one dependent variable. The results show that the variables of the recruitment process, working conditions and environment, and the information technology have a significant positive effect on retaining employees.